Teacher identity and agency in an era of accountability - Buchanan, Rebecca (Teachers and teaching, theory and practice, 2015)
The current zeitgeist in education in the USA emphasizes accountability for schools, students, and teachers, based on performance that can be easily quantified. Within this, current debates involving who should be teaching, what a good teacher looks like, and how best to evaluate and reward teachers are actually debates about the teaching profession. Inside such social and policy debates, however, lie real teachers with complex professional selves. The qualitative study reported here investigated how primary school teachers constructed self-understandings of what it means to be a professional inside the current educational reform context in the USA. Drawing from social-practice theories of identity construction and conceiving of the current educational reform discourses as sets of diffuse force relations that shape the social contexts and conditions of possibility in which American teachers work, this study sought to understand how nine California teachers made sense of their own professional selves amid the reform climate. With a special focus on professional agency, this article uses teacher identity to examine the interplay of how teachers are shaped by reform contexts and discourses, as well as how they resist and negotiate in order to create a place for themselves in both their schools and the current national policy and reform climate.